PERANAN SATUAN POLISI PAMONG PRAJA DALAM MENEGAKKAN PERATURAN DAERAH NOMOR 08 TAHUN 2018 (Studi Kasus Pedagang Kaki Lima) KECAMATAN TANJUNG KABUPATEN TABALONG (JAPB, 2022)
ABSTRACT The Civil Service Police Unit is a government apparatus, especially in the regions, with the task of helping regional heads implement regional regulations, maintain public order and public peace, and organize community protection, regulated in government regulation number 08 of 2018. In carrying out their duties, Satpol PP often has to face various obstacles when they have to deal with people who have particular interests, such as having to maintain their profession as vagrants or beggars, cadgers, and so on to fight for their lives, which ultimately leads to conflicts (clashes). The purpose of this study was to determine and analyze the role of the Civil Service Police Unit in controlling cadger. The data collection technique in this study used interview techniques consisting of 15 informants. This study uses qualitative methods with descriptive analysis. The data collection method in this study was the observation, interviews, and documentation. The data analysis method uses an interactive analysis model by Miles and Huberman. The study results indicate that (1) Satpol PP has succeeded in controlling cadger without clashes through preventive, prosecution, and repressive measures. (2) Satpol PP can enforce regional regulations and maintain order and neatness in the beauty of Tanjung City. Keywords: Role, Civil Service Police Unit, Regional Regulation